2020
DOI: 10.1136/bmjopen-2019-032620
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting somatostatin analogue treatments in autosomal dominant polycystic kidney disease and polycystic liver disease: a systematic review and meta-analysis

Abstract: ObjectivesA number of randomised control trials (RCTs) investigating the effects of long-acting somatostatin analogues in autosomal dominant polycystic kidney disease (ADPKD) and polycystic liver disease (PLD) have been recently reported. We sought to evaluate all available RCTs investigating the efficacy of somatostatin analogues treatment in ADPKD and PLD.Data sourcesElectronic databases; Pubmed, Clincaltrials.gov and Cochrane Central Register of Controlled TrialsEligibility criteria for selecting studiesRCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…However, the body of evidence has continued to grow and this meta-analysis did not analyzed the effect of these drugs on the total liver volume (TLV). Another previous meta-analysis reported that somatostatin analogs attenuated TLV, but it did not show demonstrated an improvement in TKV and eGFR [22]. This last study used absolute volumes of kidney and liver which may lead to an under-or overestimated effect size due to highly heterogeneous baseline volumes between studies.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the body of evidence has continued to grow and this meta-analysis did not analyzed the effect of these drugs on the total liver volume (TLV). Another previous meta-analysis reported that somatostatin analogs attenuated TLV, but it did not show demonstrated an improvement in TKV and eGFR [22]. This last study used absolute volumes of kidney and liver which may lead to an under-or overestimated effect size due to highly heterogeneous baseline volumes between studies.…”
Section: Introductionmentioning
confidence: 88%
“…Compared with a previous meta-analysis, we estimated the effect of somatostatin analogues on TLV or TKV using the change in percentage instead of absolute values [22]. We considered this methodology more appropriate because baseline TLV or TKV is highly heterogeneous among studies and therefore the analysis could be over-or under-estimated, and this could lead to inaccurate efficacy estimates.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ), findings consistent with those in a previous in vivo study 33 . In contrast, CaSR is also expressed in hepatocytes 38 , 39 and a recent meta-analysis revealed that somatostatin analogue treatment improved total liver volume in ADPKD patients 40 . Thus, cinacalcet may also have effects on liver cysts, though additional studies are needed to assess such effects in ADPKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKA by cAMP also elicits a strong mitogenactivated protein (MAP) kinase response in ADPKD cells, which are primed to be activated by decreased cytosolic calcium caused by PKD mutation (17,19,20). As an understanding of the molecular mechanisms of ADPKD progression has grown in recent years, so has the number of potential therapies (1)(2)(3)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), including drugs that target cAMP-dependent fluid secretion and target cell growth and proliferation. One such drug is the AVP V2 receptor antagonist, tolvaptan, which has been approved by the U.S. Food and Drug Administration (FDA) for the treatment of adult patients with ADPKD (17,(35)(36)(37)(38)(39); however, high cost and side effects, including polyuria, nocturia, thirst, and liver complications limit its use in some patients.…”
Section: Introductionmentioning
confidence: 99%